KECERMATAN PENULISAN KATA BAKU OLEH GURU-GURU SMA NEGERI 1 KUPANG TENGAH - Hendrik Jehane; Fransiskus Sanda; Jeladu Kosmas (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2020)
To commemorate the Language Month and Youth Oath, October 28, 1928, the counseling team took the initiative to conduct an Indonesian language counseling for teachers of SMA Negeri 1 Kupang Tengah. The target of this counseling is teachers because all subject teachers in schools have the same responsibilities as Indonesian language teachers. The teacher is a good model of using Indonesian language for students. The problems faced by PPM partners are (1) teachers are not yet aware of the role of Indonesian as a vehicle for unifying the nation, unifying various tribes with local languages ​​living in Indonesia; (2) there are still many teachers who think that learning Indonesian in schools is the responsibility of Indonesian language teachers, even though it should be the responsibility of all subject teachers; (3) teachers are not yet aware of the important role of Indonesian as a window to the world or as a vehicle for knowledge; (4) there are still many teachers who have not been careful in writing absorption words or original Indonesian words, writing affixed words, and so on. The purpose of this counseling is that the participants have the competence of an attitude of respecting the Indonesian language as a unifying tool for the nation and as a vehicle for knowledge, and are proficient in using Indonesian language that is good and right in various domains of language use.Outreach shows that the teachers of SMA Negeri 1 Kupang Tengah expressed satisfaction with this counseling. They realize that so far they are not aware of the important role and function of the Indonesian language as a unifying tool for the nation and as a vehicle for knowledge. They also realize that so far they do not care and are not careful in speaking Indonesian. This counseling is very useful for them. Before being given counseling the teachers of SMAN 1 Kupang were only mastering 50, 43% of the material discussed in the extension. But after being given counseling, their mastery level of counseling materials reached 85.96%. This shows that this counseling has succeeded in increasing the competence of teachers and education personnel in SMA Negeri 1 Kupang Tengah in using standard Indonesian.